2001
DOI: 10.1097/00000658-200109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigms and Improved Results for the Surgical Treatment of Acute Type A Dissection

Abstract: ObjectiveTo examine the effect of an integrated surgical approach to the treatment of acute type A dissections. Summary Background DataAcute type A dissection requires surgery to prevent death from proximal aortic rupture or malperfusion. Most series of the past decade have reported a death rate in the range of 15% to 30%. MethodsFrom January 1994 to March 2001, 104 consecutive patients underwent repair of acute type A dissection. All had an integrated operative management as follows: intraoperative transesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 27 publications
2
113
1
3
Order By: Relevance
“…It should also be acknowledged that the small sample size of our single-institution experience limits the utility of statistical comparisons of mortality rates and volume trends between time intervals. Nonetheless, we consider a 30-day/in-hospital ATAAD repair operative mortality rate of 10% or less to be the current benchmark number for high-volume aortic centers and the general target number for our program (27,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be acknowledged that the small sample size of our single-institution experience limits the utility of statistical comparisons of mortality rates and volume trends between time intervals. Nonetheless, we consider a 30-day/in-hospital ATAAD repair operative mortality rate of 10% or less to be the current benchmark number for high-volume aortic centers and the general target number for our program (27,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Solu-Medrol (1 gram, intravenously) is administered for pharmacologic neuroprotection to all patients preoperatively. The standard operation involves aortic valve resuspension with ascending aorta and hemiarch replacement (26,27). Aortic root replacement is performed selectively for aortic root aneurysm, intrinsic aortic valve pathology not amenable to repair, or extensive destruction of the intima of the aortic root by the dissection process.…”
Section: Patient Selection and Operative Techniquementioning
confidence: 99%
“…Our study found no difference in operative mortality with respect to ACP, RCP or DHCA during repair of acute type A aortic dissection. Other studies have also concluded that there is no difference in operative mortality between ACP and RCP (10,(14)(15)(16). While the method of cerebral perfusion may be a less important predictor of operative mortality, cerebral perfusion in general seems to be important for minimizing mortality.…”
Section: Operative Mortalitymentioning
confidence: 98%
“…RCP patients demonstrated a trend towards a higher rate of postoperative stroke that may be attributed to the fact that more patients in the RCP group had a history of cerebrovascular accident. Other studies have also demonstrated no difference between RCP and ACP for postoperative stroke; however, RCP tended to have more cases of transient neurological damage (4,6,12,14). The most important risk factors for stroke are circulatory arrest time over 40 minutes and prolonged CPB time (15).…”
Section: Cerebral Protection Strategy and Risk Of Strokementioning
confidence: 99%
“…Bavaria and colleagues demonstrated a significant improvement over previous reported series of Type A aortic dissection repairs using DHCA and RCP. In their series of 104 patients, these investigators reported a 9% mortality rate and 5% stroke rate with a mean duration of DHCA+RCP of 42 minutes in 104 consecutive patients undergoing emergent repair of Type A aortic dissection (27). In a series of 479 patients undergoing arch surgery with DHCA for aneurysmal disease or dissection, Coselli compared the results using DHCA alone vs. DHCA+RCP.…”
Section: Retrograde Cerebral Perfusionmentioning
confidence: 99%